2008
DOI: 10.1093/jxb/ern248
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, gene structures, and expression patterns of the ERF gene family in soybean (Glycine max L.)

Abstract: Members of the ERF transcription factor family play important roles in regulating gene expression in response to biotic and abiotic stresses. In soybean (Glycine max L.), however, only a few ERF genes have been studied so far. In this study, 98 unigenes that contained a complete AP2/ERF domain were identified from 63 676 unique sequences in the DFCI Soybean Gene Index database. The phylogeny, gene structures, and putative conserved motifs in soybean ERF proteins were analysed, and compared with those of Arabid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
183
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(187 citation statements)
references
References 58 publications
3
183
0
1
Order By: Relevance
“…5a, b). The results raised the question whether other ERF genes encoding EAR motif-containing proteins would have the ability to induce cell death when overexpressed, because many ERF genes encoding the EAR motif-containing proteins have been reported for various plant species (Nakano et al 2006;Ohta et al 2001;Zhang et al 2008). Two genes, OsERF#074 (DDBJ accession AK111755) and OsERF#075 (DDBJ accession AK069262, reported as OsERF3) were isolated from a monocotyledonous plant, O. sativa, based on nucleotide sequence information (Nakano et al 2006).…”
Section: Overexpression Of Nterf3 Induces Hr-like Cell Death In Tobaccomentioning
confidence: 99%
See 1 more Smart Citation
“…5a, b). The results raised the question whether other ERF genes encoding EAR motif-containing proteins would have the ability to induce cell death when overexpressed, because many ERF genes encoding the EAR motif-containing proteins have been reported for various plant species (Nakano et al 2006;Ohta et al 2001;Zhang et al 2008). Two genes, OsERF#074 (DDBJ accession AK111755) and OsERF#075 (DDBJ accession AK069262, reported as OsERF3) were isolated from a monocotyledonous plant, O. sativa, based on nucleotide sequence information (Nakano et al 2006).…”
Section: Overexpression Of Nterf3 Induces Hr-like Cell Death In Tobaccomentioning
confidence: 99%
“…Plants have evolved many plant-specific transcription factors to precisely regulate the expression of their genes. Among them, the AP2/ERF superfamily is one of the largest families of transcription factors in plants (Nakano et al 2006;Zhang et al 2008;Zhuang et al 2011). Ethylene response factors (ERFs) bind with high affinity to the conserved promoter sequence, called the GCC-box through the highly conserved AP2/ERF domain (Hao et al 1998;Ohme-Takagi and Shinshi 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that overexpression of certain genes is required to adapt to stress at the physiological and biochemical levels. The transcription factor APETALA2/ethylene response factor (AP2/ ERF), characterized by a 57-66-amino acid AP2/ERF DNA-binding domain, plays an important role in the regulation of biotic and abiotic stress-responsive gene expression (Okamuro et al, 1997;Sakuma et al, 2002;Zhang et al, 2008). Based on sequence similarity and the structure of the AP2/ ERF domains, the AP2/ERF superfamily, apart from one gene (At4g13040), can be divided into 3 main families: 1) AP2, 2) ERF, and 3) RAV (Nakano et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the recent findings is presented below and in Table 1. AP2/ERF AP2/ERF transcription factors can be classified into 5 subfamilies including the AP2 (APETALA2), ERF (ethylene-responsive transcription factor), DREB (dehydration-responsive element-binding protein), RAV (related to ABI3/VP1), and Soloist (Sakuma et al, 2002;Zhuang et al, 2009) depending on the number of AP2/EFR domain. More than 380 AP2/ERF genes are present in the soybean genome (Mochida et al, 2009;Wang et al, 2010b) while only a few of them have been characterized (Gao et al, 2005;Li et al, 2005;Chen et al, 2006;Chen et al, 2007;Mazarei et al, 2007;Wang et al, 2008;Zhang et al, 2008b;Chen et al, 2009a;Zhang et al, 2009a;Zhang et al, 2009b;Zhuang et al, 2009;El Ouakfaoui et al, 2010;Jin et al, 2010). More than 10 members of the gene family encoding DREB transcription factors present in the soybean genome (Phang et al, 2008), and 7 of the GmDREB genes are induced by ABA, salt, drought, and/or cold stress (Table 1) (Gao et al, 2005;Li et al, 2005;Chen et al, 2006;Chen et al, 2007;Chen et al, 2009a;Jin et al, 2010).…”
Section: Transcription Factors Participated In Osmotic Stress Signallmentioning
confidence: 99%